Field dynamics in Layered Cylinder Resonator - Romero-Antequera, David L.; Sánchez Mondragón, J. J. (Acta Universitaria, 2013)
We present the field dynamics in a layered cylinder resonator. The resonators can be regarded as concentric ring resonators. We found that it is possible to excite the rings with clockwise and counterclockwise modes, and these modes can be separated promoting the coupling of each of these to the output ports of the buffers of the resonators.
Keywords: Array; Array; Array